Advances in the surgical treatment of Crohn's disease - Antonio Luberto; Annalisa Maroli; Michele Carvello; Antonino Spinelli (Publicaciones Permanyer, 2022)
Despite the advances in medical treatment of Crohn's disease (CD), most of the patients require one or more surgical bowel resections during their life for complicated disease. Surgery for CD has gone through progressive technical refinement over time. Minimally invasive surgery and bowel-sparing techniques have been validated with regard to surgical trauma reduction, and their role has been clearly defined in the current guidelines. Nevertheless, continuous technology advancement has further expanded the surgical tools with single-access and robotic-assisted surgery. With the aim of further reducing the impact of surgery, the concept of "strategic surgery" has been explored. On the one hand, patients' optimization before surgery has the potential to reduce post-operative complications. On the other, early intervention for the uncomplicated disease before medical therapy escalation has been demonstrated equally reliable with respect to biologics in terms of quality of life and advantageous in terms of health-care costs. Ultimately, a better comprehension of the pathological mechanisms underlying the disease is the key to radically changing the surgical management of both abdominal and perianal CDs. In fact, novel surgical strategies aiming at reducing disease recurrence which take into account the anastomotic configuration and the role of the mesentery as an active player in the disease process have been pursued in the past decade. The purpose of this review is to describe the recent innovations in the surgical treatment of CD focusing on their potential impact on the short- and long-term outcomes.